Inventarisasi Serangga Pada Pertanaman Jeruk Nipis (Citrus Aurantifali) di Desa Plosogenuk Kecamatan Perak Kabupaten Jombang - Wahyu Rizqilillah Putra; Siti Aminatuz Zuhria; Arifah Roosenani (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
This research was conducted at September – November 2020 with the aim of knowing the types of pests and diseases that predominantly attack lime in Perak District, Jombang Regency. This research is descriptive quantitative, namely direct sampling from the observation location, using traps such as trap holes, trap nets and direct observations on lime plantations. Sampling of all plants will be the sampling point (30 plants. Observations were made 10 repetitions, with an observation time interval of 3 days. The pest data obtained were identified and analyzed using the abundance index (K) and Dominant index (C) formulas. The pest identification study obtained 504 individuals consisting of 6 species. The highest insect abundance (K) value was found in the Coccidae family with the Order Homoptera, which was 53,968. The dominance index value was 0.29 indicating the result that there was no dominant family in this study planting.